PSYCHOLOGICAL CONDITION OF THE FAMILY AS DRUGS SUPERVISOR - Iskim Luthfa; Dwi Aprianti (Fakultas Ilmu Keperawatan Universitas Islam Sultan Agung, Semarang, 2018)
DOTS is a government program in controlling tuberculosis. One of the components of DOTS is the Drugs Supervisor (DS). Families as DS will be at risk of experiencing psychological problems. The purpose of the study was to determine the psychological condition of the family as a DS in the Semarang City Health Center. This study uses mixed methods with sequential explanatory design. The research sample was taken in total as many as 110 families as DS. Instrument for measuring anxiety using the Zung Self-Rating Anxiety Scale (ZSRAS), instrument for measuring stress levels using the Kingston Caregiver Stress Scale (KCSS). Data analysis uses a spearman rank. All respondents (100%) experienced mild anxiety levels, and 83 respondents (75.5%) experienced mild stress levels. The test results obtained p value 0.004 <0.05, and r value 0.274. There is a relationship between anxiety and stress, the higher the level of anxiety, the higher the stress level of the family as a DS.